A Calcineurin Regulator MoRCN1 Is Important for Asexual Development, Stress Response, and Plant Infection of Magnaporthe oryzae - Liu, Caiyun; Liu, Tiangu; Lv, Ziwei; Qin, Mengyuan; Qu, Zhiguang; Zhang, Ziwei; Li, Fuyan; Chen, Deng; Zhang, Xinrong; Chen, Xiao-Lin; Shen, Mi (Frontiers in Plant Science, 2022)
The calcium/calcineurin signaling pathway plays key roles in development and virulence of the plant pathogenic fungi, but the regulation of this signaling pathway is still not clear. In this study, we identified a calcineurin regulator MoRCN1 in the plant pathogenic fungus Magnaporthe oryzae, and found it is important for virulence by regulating the calcineurin pathway. The MoRCN1 deletion mutants were severely decreased in colony growth and conidia formation. More importantly, deletion of MoRCN1 led to significant reduction of virulence, due to defects in appressorium formation and invasive growth. The ΔMorcn1 mutants were more sensitive to different stresses and induced host ROS accumulation, suggesting a role of MoRCN1 in stress adaptation. We found that MoRCN1 directly interacted with the calcineurin catalytic subunit MoCNA and affected its protein stability, therefore was important for regulating the calcineurin pathway. Transcriptome analysis showed that MoRCN1 significantly activated 491 genes and suppress 337 genes in responding to calcium ion, partially overlapped to the MoCRZ1-bound genes. Gene ontology and KEGG pathway analyses indicated that MoRCN1-regulated genes were enriched in stress adaptation, lipid metabolism, and secondary metabolites biosynthesis, reflecting a function of MoRCN1 in host cell adaptation. Altogether, these results suggested MoRCN1 functions as a regulator of calcium/calcineurin signaling pathway for fungal development and infection to host cell.